2016
DOI: 10.1371/journal.pone.0160101
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Functional Properties of Wheat Gluten Using Acid Protease from Aspergillus usamii

Abstract: Hydrolysis parameters (temperature, E/S ratio, pH, and time) for acid protease (from Aspergillus usamii) hydrolysis of wheat gluten were optimized by response surface methodology (RSM) using emulsifying activity index (EAI) as the response factor. A temperature of 48.9°C, E/S ratio of 1.60%, pH 3.0, hydrolysis time of 2.5 h was found to be the optimum condition to obtain wheat gluten hydrolysate with higher EAI. The solubility of wheat gluten was greatly improved by hydrolysis and became independent of pH over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…The hydrolysis length may be assessed by the HD, which also can indicate longer or shorter lengths of the peptide chain. Previous studies showed <30% values of HD in others protein hydrolysates by the use of a single enzyme [7]. The HD outcomes of WGPC treated with Alcalase after 0, 15, 30, 45, and 60 min is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The hydrolysis length may be assessed by the HD, which also can indicate longer or shorter lengths of the peptide chain. Previous studies showed <30% values of HD in others protein hydrolysates by the use of a single enzyme [7]. The HD outcomes of WGPC treated with Alcalase after 0, 15, 30, 45, and 60 min is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 89%
“…Wheat is consumed worldwide and is a cultivated cereal and it is the basic food in the human diet through bread consumption. Wheat gluten (WG) is an economically important co-product in the recovery of wheat starch in wet milling of wheat flour [7]. Currently, wheat protein is used in animal and human nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The improvements in these properties caused by papain treatment could be explained by its nonspecific proteolytic action, that is, papain cleaves at random, opening the structure of the protein. An increase in both WHC and OHC with enzyme hydrolysis has been reported for wheat gluten using Aspergillus usamii (Deng et al, 2016), rapeseed protein using Alcalase and protease from B. licheniformis (Vioque, Sanchez-Vioque, Clemente, Pedroche, & Millan, 2000), kidney bean using papain (Wani, Sogi, Shivare, & Gill, 2015), and OHC but not WHC for pea flour using protease from Aspergillus saitoi (Periago et al, 1998). Miedzianka et al (2014) reported a large increase in OHC for potato protein concentrate modified with Alcalase, but a severe decrease in the WHC due to the high solubility of the modified protein.…”
Section: Water-and Oil-holding Capacitiesmentioning
confidence: 99%
“…A previous report on hydrolyzed gluten suggested that SS content increases due to because SH groups oxidized to SS bonds at acidic pH on heating (Shewry & Tatham, 1997). To unfold the globular structure of protein as well as to stabilize the structure of smaller peptides, enzymatic hydrolysis disrupts the SS bonds and generates new SS bonds among both original unpaired SH and newly generated SH (Deng et al., 2016).…”
Section: Resultsmentioning
confidence: 99%